Motyw światła i ciemności w mistyce Pseudo-Makarego - Uciecha, Andrzej (Verbum Vitae, 2016)
The aim of this article was to familiarize the reader with the imagery of light, particularly its role in the development of ascetic discipline and early Christian mysticism. The vehicle for this exploration is an analysis of selected texts from the spiritual collection of the monk and hermit Pseudo-Macarius (Symeon of Mesopotamia). In Macarius’s theology of light one may find clear references to the thought of Origen, as well as the influence of other Church writers representing the heritage of both Greek Alexandrian tradition and Syrian thought. The theological message of Symeon of Mesopotamia should be read in the pneumatological context. The fundamental truth of his spiritual homilies is communion in Holy Spirit and the reception of His fullness. In the article, the author seeks to elucidate and interpret the spiritual tradition known to researchers as une mystique pneumatique. The homilies of Macarius significantly contributed to the dissemination of this pneumatological mysticism throughout the Greek and later Byzantine world. The interesting apologetic themes appear on the margins of the main subject of the works and are very superficially discussed in the context of the general polemics with heresies.